O projeto de desenvolvimento econômico chinês - 1978-2008: a singularidade de seus fatores políticos e econômicos - Leite, Alexandre César Cunha (2011)
Over the past 30 years China is presenting itself to the international context as a nation of remarkable economic dynamism and, simultaneously, has been the scene of major socio-political transformations in its internal landscape. Its trajectory of great economic growth, international insertion and sovereign calls attention to the emergence of a new power. This thesis was concerned to understand the Chinese national development project, defining its inflection point as the year of 1978 and limiting the temporal scope of the study to the year 2008. To achieve this objective, descriptive and analytical efforts were divided into four chapters. The first chapter presents a brief history of the period, with the greatest concern of the major political, economic and, social events, which changes that shaped the internal landscape of China. It is intended to describe the scenario this way the structural transformation of China which will be described and evaluated in the following chapters, all focused on understanding the composition of a development project in China and in confirming the hypothesis of the thesis that China cannot be seen as a role model because of their idiosyncrasies and peculiarities in virtually all areas of society that make it up. The second chapter discusses the concepts of sovereignty and security in the Chinese context to the theoretical contribution and its past. Made this reflection and realizing the magnitude of these concepts to Chinese scenery and within the proposed of national development political and economic with sovereign and autonomous, we proceed to the discussion of its emergence as a regional power and the repercussions of this movement to international politics. The third chapter seeks to report and speculate about the great changes and policy changes implemented in China in the post-1978, with the rise of Deng Xiaoping, and how such changes influenced policy in achieving its goals guided by its proposal for national development. Still, it was possible the coexistence of a particular political model, characterized by a state-party with capitalist practices adopted in order to better tailor its proposal for international insertion. Finally, the fourth chapter, we assessed quantitatively and qualitatively the progression of economic and social data to China that led to this level of development, including also its consistency, but above all its particularities that allow the classification of the China´s national project of development as unique. We conclude this thesis confirms the original hypothesis of uniqueness of the Chinese case, your development project and his experience can contribute to the development of other emerging nations, but by no means become a model to be reproduced by other nations because their particularities and their internal form of adoption